Safety, Feasibility, and Acceptability of the PrePex Device for Adult Male Circumcision in Malawi. (1st June 2016) - Kohler, Pamela K.; Tippett Barr, Beth A.; Kang'ombe, Anderson; Hofstee, Carola; Kilembe, Franklin; Galagan, Sean; Chilongozi, David; Namate, Dorothy; Machaya, Medson; Kabwere, Khuliena; Mwale, Mwawi; Msunguma, Wezi; et al.
Abstract : Introduction: Nonsurgical adult male circumcision devices present an alternative to surgery where health resources are limited. This study aimed to assess the safety, feasibility, and acceptability of the PrePex device for adult male circumcision in Malawi. Methods: A prospective single-arm cohort study was conducted at 3 sites (1 urban static, 1 rural static, 1 rural tent) in Malawi. Adverse event (AE) outcomes were stratified to include/exclude pain, and confidence intervals (CIs) were corrected for clinic-level clustering. Results: Among 935 men screened, 131 (14.0%) were not eligible, 13 (1.4%) withdrew before placement, and 791 (84.6%) received the device. Moderate and severe AEs totaled 7.1% including pain [95% CI: 3.4–14.7] and 4.0% excluding pain (95% CI: 2.6 to 6.4). Severe AEs included pain (n = 3), insufficient skin removal (n = 4), and early removal (n = 4). Among early removals, 1 had immediate surgical circumcision, 1 had surgery after 48 hours of observation, 1 declined surgery, and 1 did not return to our site although presented at a nearby clinic. More than half of men (51.9%) reported odor; however, few (2.2%) stated they would not recommend the device to others because of odor. Median levels of reported pain (scale, 1–10) were 2 (interquartile range, 2–4) during application and removal, and 0 (interquartile range, 0–2) at all other time points. Conclusions: Severe AEs were rare and similar to other programs. Immediate provision of surgical services after displacement or early removal proved a challenge. Cases of insufficient skin removal were linked to poor technique, suggesting provider training requires reinforcement and supervision.